(untitled) (Scientific journal of the Fergana State University, 2023)
This article presents the results of differential heats and entropy of adsorption of toluene in CuZSM-5 zeolite. For measurements of isotherms and differential heat of adsorption, a system consisting of a universal high-vacuum adsorption unit and an attached differential modified Tian-Calve microcalorimeter DAC-1-1A was used to provide direct quantitative and qualitative characteristics of the nature and forces of adsorption interaction. The correlation between the adsorption-energy characteristics was found and the molecular mechanism of toluene adsorption in CuZSM-5 zeolite in the whole filling region was revealed. Toluene adsorbed in CuZSM-5 zeolite is located in the first coordination sphere with Cu2+ cation, forming two-dimensional complexes. It was found that the charge density significantly affects the mechanism, the energy of adsorption and the number of adsorbed molecules. It was determined that the average molar entropy of toluene adsorption in CuZSM-5 zeolite indicates that the mobility of toluene molecules in zeolite is below the liquid phase and close to that of the solid phase, indicating that the mobility of toluene molecules on cations is strongly inhibited.